2020
DOI: 10.3390/ijms22010315
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Opioid Receptors in Cells of the Immune System

Abstract: The observation of the immunomodulatory effects of opioid drugs opened the discussion about possible mechanisms of action and led researchers to consider the presence of opioid receptors (OR) in cells of the immune system. To date, numerous studies analyzing the expression of OR subtypes in animal and human immune cells have been performed. Some of them confirmed the expression of OR at both the mRNA and protein level, while others did not detect the receptor mRNA either. Although this topic remains controvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 106 publications
(104 reference statements)
0
29
1
2
Order By: Relevance
“…The KOR has been demonstrated on thymoma cell lines, macrophage cells lines, splenocytes, PBMC, T‐cell and B‐cell lines, and NK cells. The NOR receptor can be found on T, B, and monocyte cell lines in humans as well as NK cells and PBMCs 15 . Although most literature surrounding opioid effects in immunologic responses has evaluated the utilization of morphine, numerous trials have demonstrated an impact of several opioid‐like agents on immune function.…”
Section: Methodsmentioning
confidence: 99%
“…The KOR has been demonstrated on thymoma cell lines, macrophage cells lines, splenocytes, PBMC, T‐cell and B‐cell lines, and NK cells. The NOR receptor can be found on T, B, and monocyte cell lines in humans as well as NK cells and PBMCs 15 . Although most literature surrounding opioid effects in immunologic responses has evaluated the utilization of morphine, numerous trials have demonstrated an impact of several opioid‐like agents on immune function.…”
Section: Methodsmentioning
confidence: 99%
“…Care should be taken as both antibiotics and NSAIDs may affect the results of the investigations. Opioids can be used as an alternative as they act on the pain perception in the brain, and some studies have shown some immunomodulatory effects from the opioid treatment used in experimental animals [ 53 ]. It is a disadvantage that opioids have a shorter half-life than NSAIDs [ 54 ].…”
Section: Analgesia and Humane Endpoints After Inoculationmentioning
confidence: 99%
“…Met-enkephalin shows high affinity for DORs and MORs, and as the latter predominate in the NAc, the main met-enkephalin activity in this brain area is mediated by them [131]. The expression of opioid receptors by immune cells has recently been reviewed [132], and it is noteworthy that inducible expression of DORs and MORs was described in rat spleen lymphocytes following Con A stimulation [133]. Met-enkephalin also interacts with the opioid growth factor receptor to delay passage through the G 1/S interface of the cell cycle and, as such, it is considered an important homeostatic regulator that influences the onset and progression of autoimmune diseases and cancer [134].…”
Section: Enkephalins 221 Enkephalins As Neuro-and Immune-modulatorsmentioning
confidence: 99%
“…This bell-shaped dose-response curve was also described a few decades ago for other endogenous opioids peptides [158] and it indicates the involvement of multiple receptors that transduce bidirectional signals that produce opposing biological effects. Thus, met-enkephalin at low concentrations seems to be proinflammatory, whereas at high concentrations it induces immunosuppression, a result of either MOR or DOR activity, respectively [132,157,159].…”
Section: Enkephalins 221 Enkephalins As Neuro-and Immune-modulatorsmentioning
confidence: 99%